METRIC CONNECTIONS ON ALMOST COMPLEX NORDEN METRIC MANIFOLDS - Teofilova, Marta (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
Two families of metric connections on almost complex Norden metric manifolds are introduced and studied. These connections are constructed by means of the two Lie 1-forms naturally existing on the manifolds. Invariant tensors under the transformations of the Levi-Civita connection into the introduced metric connections are obtained.